Membangun Komunitas Sadar Gizi Balita dan Ibu Menyusui di Desa Taratak Kota Pariaman - Untari, Puthi Dwi (Amalee: Indonesian Journal of Community Research and Engagement, 2020)
High amount of malnutrition cases in West Sumatra, especially in Pariaman City pushing the healthcare academicians to participate actively conducting the community research. STIKes Sumbar is one of them to carrying out the program of community service in Taratak village. This program was held in collaboration with the local health practitioners and implemented to provide assistance and nutrition counseling of toddlers’ nutrition and breastfeeding mothers of whom a community awareness is expected. Employing participatory action research, it is revealed that the program can accelerate the realization of the healthy toddler program. The positive impact of these activities has been also capable to support the healthy nutrition program to prevent malnutrition and stunting symptom at the village. For the coming occasion, the local health practitioners and academicians are to continue supporting this program in the effort to improve public health, and to prevent the malnutrition. Keywords: Breastfeeding mothers, malnutrition, stunting, toddlers’ nutrition-conscious community Abstrak Tingginya jumlah kasus gizi buruk di Sumatera Barat, khususnya di Kota Pariaman mendorong akademisi layanan kesehatan untuk berpartisipasi aktif melakukan penelitian masyarakat. STIKes Sumbar adalah salah satunya yang melaksanakan program pengabdian masyarakat di desa Taratak. Program ini diselenggarakan bekerja sama dengan praktisi kesehatan setempat dan dilaksanakan untuk memberikan bantuan dan konseling gizi bagi para balita dan ibu menyusui. Dengan menggunakan penelitian tindakan partisipatif, tampak bahwa program ini dapat mempercepat realisasi program balita sehat. Dampak positif dari kegiatan ini juga mampu mendukung program gizi sehat untuk mencegah malnutrisi dan gejala stunting di desa setempat. Untuk kesempatan mendatang, praktisi kesehatan dan akademisi diharapkan terus mendukung program ini dalam upaya meningkatkan kesehatan masyarakat serta untuk mencegah kekurangan gizi. Kata kunci: Ibu Menyusui, komunitas sadar gizi balita, malnutrisi, stunting